Is Asia Prepared for an Aging Population? - Heller, Peter (Washington, D.C. : International Monetary Fund, 2006)
Many Asian countries (such as China, Singapore, Korea, Thailand, Malaysia, Indonesia, India, and the Philippines) will experience a significant aging of their populations during the next several decades. This paper explores how these aging Asian countries are addressing and anticipating the challenges of an aging society. It suggests that Asia's preparedness for an aging population is decidedly mixed. While growth policies have been successful, much work is still needed in many countries to establish an adequate and farsighted policy framework in the areas of pensions, health insurance, and labor market policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet